Reflections: Insomnia? Try Counting Leadership Theories - Higgs, Malcolm (Journal of change management, 2022)
40 years ago, it was argued that despite years of research we still did not understand leadership. A similar argument was presented in this journal just last year. This article presents some reflections based on both my experience of researching leadership and of working with leaders. In doing this the myriad of theories of leadership are explored and key trends identified. Perhaps the most significant of these is the recognition of leadership as a dynamic relational process. This enables us to move from a leader-centric focus in research to one that recognizes the active participation of followers in the leadership process. In addition, the limitations of research to date, and its lack of relevance to practice are discussed, followed by proposed actions that could be taken to help develop a clearer understanding of the nature of leadership and improve relevance for practitioners. The article concludes with the view that we do know a lot about leaders and their impact on a wide range of outcomes. However, we still know relatively little about leadership.